Epidemiological Study of Crimean–Congo Hemorrhagic Fever in Thi Qar Province from 2021 to 2023 - Aziz, Mohammed Mohsin (American Journal of Biomedicine and Pharmacy, 2025)
Background: Crimean-Congo haemorrhagic fever (CCHF) has been sporadically reported in Iraq. However, a lack of preventive veterinary measures during the three years of the COVID-19 pandemic (2021, 2022, 2023) resulted in the largest CCHF outbreak in the country since 1979. Study Objective: The study aimed to describe the epidemiological characteristics of CCHF cases in Thi-Qar province during 2021, 2022, and 2023, focusing on age, sex, residence, and history of contact with animals. Materials and Methods: Data for this study were sourced from the Thi-Qar Veterinary Hospital’s educational records. The research focused on laboratory-confirmed CCHF cases reported during three periods: July 7 to December 16, 2021; March 29 to December 11, 2022; and January 2 to December 4, 2023. Frequencies and percentages were used to describe demographic and epidemiological patterns. The epidemic curve was analyzed to illustrate the timing and duration of the outbreak. Results: A total of 315 cases of CCHF were confirmed by the Iraq Central Public Health Laboratory using polymerase chain reaction (PCR) testing between July 7, 2021, and December 4, 2023. The first confirmed case was reported on July 3, 2021, with cases continuing through December 2023. Most cases were males (n=180, 57.14%) and resided in Nasiriyah Center (n=85, 27%). The first case emerged in the 28th week of 2021. Case numbers peaked in the 20th week of 2022, with 64 cases reported, before gradually declining to only two cases by the 53rd week of 2023. The overall case fatality rate for the period was 17.7%. Conclusion and Recommendations: The 2022 outbreak was the largest CCHF outbreak in Iraq since the disease was first documented over 40 years ago. Further identification of CCHF strains in Iraq is essential. Additionally, a national survey of CCHF vectors, along with studies exploring the knowledge, attitudes, and practices of high-risk groups, is strongly recommended to better understand and mitigate future outbreaks.